Church Communication through Websites of Bishops’ Conferences - Pavel Izrael; Petra Polievková (Religions, 2024)
This study investigates the role of conferences of bishops’ websites in facilitating communication within the Catholic Church, focusing on selected countries. The aim is to assess how these websites align with the Church’s mission and engage diverse audiences in the digital age. Analysis of websites from Slovakia, Poland, and the Czech Republic reveals variations in content emphasis, multilingual accessibility, multimedia utilization, and social media integration. These differences reflect cultural and ecclesiastical distinctions, shedding light on how these websites serve as digital gateways to the Catholic Church and public-facing portals for their respective conferences. This research employs the website communication model (WCM) to assess the selected websites. It examines content elements, multilingual support, multimedia incorporation, and social media presence. This study underscores the potential for enhanced utilization of digital platforms in advancing the Church’s mission and expanding its outreach. It highlights the importance of aligning website goals with organizational objectives and engaging diverse audiences effectively. Ultimately, these websites serve as crucial tools for communication, evangelization, and pastoral care within the Catholic Church.